Vietnam's Extraordinary Performance in the PISA Assessment: A Cultural Explanation of an Education Paradox - Niaz Asadullah; Liyanage Devangi Perera; Saizi Xiao (Institute of Labor Economics (IZA), 2020)
This paper examines the nature and drivers of Vietnam's paradoxical performance in the Program for International Student Assessment (PISA) – consistently high student achievement despite being the poorest of all participating countries and a centralized education system. We first document 'Vietnam advantage' in a wide-range of supply and demand-related indicators such as school participation rate, educational inequality, inputs and expenditure in cross-country regression models. We then estimate an augmented educational production function to show that these supply and demand-side advantages don't explain away Vietnam's positive deviance in PISA when compared to other participating developing and developed countries. We then conduct student-level analysis to examine Vietnam's performance in PISA 2012 in a regional context, vis-a-vis three high-spending but low-performing ASEAN member countries (Malaysia, Indonesia and Thailand) and two high performing Asian countries (South Korea and Singapore). Pooled regression estimates show that, holding differences in various indices of socioeconomic background, the gap in average student test scores between Vietnam and South Korea in Reading and Science becomes statistically insignificant. Moreover, once school-specific differences are also accounted for, Vietnamese students do just as well as Singaporean across all subjects — equalizing for existing socioeconomic differences between countries would give Vietnam an even better advantage in the PISA. A similar gain in PISA scores is absent in the case of Malaysia, Indonesia and Thailand. The paper concludes by offering a cultural explanation for the significant variation in educational performance among high-spending East Asian countries.
Keywords: A20; I21; I28; 330; ASEAN; Confucian culture; expenditure policy; school quality; Malaysia